Menavigasi Keuangan Digital: Pengaruh Literasi Fintech, Persepsi Risiko, dan Layanan yang Dipersonalisasi terhadap Adopsi Fintech - Jocelyn Patricia; Christian Tanjaya; Susan Susan; Yeni Ariesa; Rusiadi Rusiadi (AKUA: Jurnal Akuntansi dan Keuangan, 2026)
The condition of MSMEs in Medan city has a rapid growth condition. Fintech adoption is vital for MSMEs in taking the broader market,,efficiency, and powerassaing through personalized services is motivated by the intention to analyze how the influence of fintech literacy, risk perception, and personalized services on fintech adoption by MSMEs in Medan City. Research methods using quantitative. The population in the study was 2,070 MSMEs in Medan City based on data from the Office of Cooperatives and MSMEs in 2025. For the number of research samples as many as 335 MSMEs using the slovin formula, then convenience sampling as a sample collection technique. Data collection techniques using questionnaires through Google form distribution to MSMEs. Data analysis techniques using Smart-PLS 3.0. Conclusions in the study obtained fintech literacy has a positive and significant effect on fintech adoption by MSMEs in Medan City, Risk Perception has a positive and significant effect on fintech adoption by MSMEs in Medan City, however, personalized services have no effect on fintech adoption by MSMEs in Medan City.